Haemodialysis withdrawal in Australia and New Zealand: a binational registry study. Issue 4 (9th August 2019) - Chan, Samuel; Marshall, Mark R; Ellis, Robert J; Ranganathan, Dwarakanathan; Hawley, Carmel M; Johnson, David W; Wolley, Martin J
Abstract: Background: Withdrawal from dialysis is an increasingly common cause of death in patients with end-stage kidney disease (ESKD). As most published reports of dialysis withdrawal have been outside the Oceania region, the aims of this study were to determine the frequency, temporal pattern and predictors of dialysis withdrawal in Australian and New Zealand patients receiving chronic haemodialysis. Methods: This study included all people with ESKD in Australia and New Zealand who commenced chronic haemodialysis between 1 January 1997 and 31 December 2016, using data from the Australia and New Zealand Dialysis and Transplant (ANZDATA) Registry. Competing risk regression models were used to identify predictors of dialysis withdrawal mortality, using non-withdrawal cause of death as the competing risk event. Results: Among 40 447 people receiving chronic haemodialysis (median age 62 years, 61% male, 9% Indigenous), dialysis withdrawal mortality rates increased from 1.02 per 100 patient-years (11% of all deaths) during the period 1997–2000 to 2.20 per 100 patient-years (32% of all deaths) during 2013–16 (P < 0.001). Variables that were significantly associated with a higher likelihood of haemodialysis withdrawal were older age {≥70 years subdistribution hazard ratio [SHR] 1.77 [95% confidence interval (CI) 1.66–1.89]; reference 60–70 years}, female sex [SHR 1.14 (95% CI 1.09–1.21)], white race [Asian SHR 0.56 (95% CI 0.49–0.65), Aboriginal and Torres Strait Islander SHR 0.83 (95% CI 0.74–0.93), Pacific Islander SHR 0.47 (95% CI 0.39–0.68), reference white race], coronary artery disease [SHR 1.18 (95% CI 1.11–1.25)], cerebrovascular disease [SHR 1.15 (95% CI 1.08–1.23)], chronic lung disease [SHR 1.13 (95% CI 1.06–1.21)] and more recent era [2013–16 SHR 3.96 (95% CI 3.56–4.48); reference 1997–2000]. Conclusions: Death due to haemodialysis withdrawal has become increasingly common in Australia and New Zealand over time. Predictors of haemodialysis withdrawal include older age, female sex, white race and haemodialysis commencement in a more recent era.